Anti-Tau Antibodies that Block Tau Aggregate Seeding In Vitro Markedly Decrease Pathology and Improve Cognition In Vivo - Yanamandra, Kiran; Kfoury, Najla; Jiang, Hong; Mahan, Thomas E.; Ma, Shengmei; Maloney, Susan E.; Wozniak, David F.; Diamond, Marc I.; Holtzman, David M. (Neuron (Cambridge, Mass.), 2013)
Tau aggregation occurs in neurodegenerative diseases including Alzheimer’s disease and many other disorders collectively termed tauopathies. trans-cellular propagation of tau pathology, mediated by extracellular tau aggregates, may underlie pathogenesis of these conditions. P301S tau transgenic mice express mutant human tau protein and develop progressive tau pathology. Using a cell-based biosensor assay, we screened anti-tau monoclonal antibodies for their ability to block seeding activity present in P301S brain lysates. We infused three effective antibodies or controls into the lateral ventricle of P301S mice for 3 months. The antibodies markedly reduced hyperphosphorylated, aggregated, and insoluble tau. They also blocked development of tau seeding activity detected in brain lysates using the biosensor assay, reduced microglial activation, and improved cognitive deficits. These data imply a central role for extracellular tau aggregates in the development of pathology. They also suggest that immunotherapy specifically designed to block trans-cellular aggregate propagation will be a productive treatment strategy. •Anti-tau antibodies block intracellular tau aggregation induced by tau seeds•Anti-tau antibodies strongly reduce tau pathology in vivo•Anti-tau antibodies decrease tau seeding activity in vivo•Anti-tau antibodies improve cognition Yanamandra et al. find that antibodies that block aggregated forms of the tau protein from entering cells and seeding further tau aggregation have beneficial effects in an animal model that is relevant for Alzheimer’s disease and related disorders.